Tingkat Kepuasan Member terhadap Profesionalisme Personal Trainer di ATLAS SPORT CLUB Surabaya - Dimas Zhafran Al Farras; Made Pramono; Soni Sulistyarto; Lutfhi Abdil Khuddus (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Fitness center is a business or service center that provides sports services and sports facilities for its customers. The level of member satisfaction can be seen from the quality of service provided. With the professionalism provided by personal trainers, members will have their own interest in the services and ethics that personal trainers do. This study aims to determine the level of member satisfaction with the professionalism provided by personal trainers at ATLAS CLUB SPORT Surabaya. This type of research is presented using a descriptive quantitative research method with a survey approach, where the questionnaire instrument is used as support for data collection. This study uses the Servqual method to measure the level of professionalism provided by personal trainers to members. This method includes several aspects, namely tangibles, reliability, responsiveness, assurance, and empathy which are used to measure the professionalism of personal trainers. The study population was members who used personal trainer services totaling 100 people, and a sample of 25 people taken using the purposive sampling method. The results of this study indicate that the tangible aspect and the responsiveness aspect received the highest scores, namely 88% and 87%. Meanwhile, the aspects of reliability, assurance, and empathy each received a score of 86%. With the results obtained, it shows that the personal trainer of ATLAS SPORT CLUB Surabaya has provided professional quality, very satisfying service and also understands what members need.